Stereoelectronic Effects in Force-Accelerated Retro-Diels–Alder Reactions - Wu, Lik Chun; De Bo, Guillaume (Synlett, 2022)
In polymer mechanochemistry, mechanosensitive molecules (mechanophores) are activated upon elongation of anchored polymer arms. The reactivity of a mechanophore can be influenced by a variety of structural factors, including the geometry of attachment of the polymer arms and the nature of eventual substituents. Here we investigate stereoelectronic effects in force-accelerated Diels–Alder reactions using the CoGEF (Constrained Geometries simulate External Force) calculation method. We found that the presence of an electron-donating heteroatom on the diene leads to a lower activation force, and that the mechanochemical reactivity is suppressed when the anchor group is attached to a central rather than lateral position.
Keywords: polymer mechanochemistry; mechanophore; force; Diels–Alder; retrocycloaddition; Hammett parameter